Recent Advances and Remaining Challenges in Perovskite Solar Cell Components for Innovative Photovoltaics - Pari Baraneedharan; Sankar Sekar; Silambarasan Murugesan; Djaloud Ahamada; Syed Ali Beer Mohamed; Youngmin Lee; Sejoon Lee (Nanomaterials)
This article reviews the latest advancements in perovskite solar cell (PSC) components for innovative photovoltaic applications. Perovskite materials have emerged as promising candidates for next-generation solar cells due to their exceptional light-absorbing capabilities and facile fabrication processes. However, limitations in their stability, scalability, and efficiency have hindered their widespread adoption. This review systematically explores recent breakthroughs in PSC components, focusing on absorbed layer engineering, electron and hole transport layers, and interface materials. In particular, it discusses novel perovskite compositions, crystal structures, and manufacturing techniques that enhance stability and scalability. Additionally, the review evaluates strategies to improve charge carrier mobility, reduce recombination, and address environmental considerations. Emphasis is placed on scalable manufacturing methods suitable for large-scale integration into existing infrastructure. This comprehensive review thus provides researchers, engineers, and policymakers with the key information needed to motivate the further advancements required for the transformative integration of PSCs into global energy production.